Disposition of the Estate of the Deceased without the Permission of the Heirs: Its Circumstances and Juristic Rulings and Its Impact on Sustainable Development - El-Sayed Abu El-Ala, Khaled Fouad (Journal of Neonatal Surgery, 2025)
The courts are witnessing claims filed by some heirs against a fellow heir who has acted concerning the estate of the deceased — such as a father or mother — without consulting them regarding the course of action undertaken. This disposition may involve directing part of the inheritance towards charitable purposes, such as donating the deceased’s vehicle to a charitable organisation, or dedicating a plot of land as a cemetery, or the disposition may be motivated by self-interest, resulting in disputes and animosity. Alternatively, the heir may sell property belonging to the deceased to a party with whom he has agreed to take a share of the proceeds, on the condition that the buyer conceals the transaction from the remaining heirs. This monopolisation of the estate — or part thereof — by one of the heirs causes psychological distress to the rest, sows enmity and resentment towards their relative who acted without their permission, disturbs social relations among them, and negatively affects economic activity and sustainable development. The Kingdom of Saudi Arabia, through its courts, prevents the proliferation of such conduct which contravenes Islamic law, civil law, and the rights of others. This research sheds light on this recurring problem in the light of the statements of jurists and their established legal maxims. The Research Objectives were represented in the following key matters: Achieving justice in the distribution of inheritance, and establishing sound relations and bonds of affection among the heirs. Establishing the concept of lawful sustenance and warning against exploiting the inheritance for unlawful gain, which would result in harm to the exploiter in his religion in the Hereafter. Clarifying the impact of an heir’s disposition of the estate without the knowledge or permission of the other heirs on social relations among members of society and on sustainable development. Demonstrating the capacity of Islamic law to find appropriate solutions for contemporary issues that arise in people's lives. This research concluded with a set of scientific findings, which are detailed at the end of the study. The research also concluded with a set of important recommendations, listed at its conclusion, that are closely connected to the subject matter.